Managing proliferative diabetic retinopathy in a patient with vitreous hemorrhage: a case report (Ukrainian Journal of Ophthalmology, 2025)
We report a case of successful treatment of a 35-year-old patient diagnosed with severe type 1 diabetes mellitus with moderate glycemic control, bilateral proliferative diabetic retinopathy and total vitreous hemorrhage in the right eye. At baseline, there was optical coherence tomography angiography and fundus photography evidence of significant neovascularization of the optic nerve and peripapillary retina along the vessels. Although Ukrainian guidelines on the use of aflibercept do not mention retinal neovascularization in diabetic retinopathy in the absence of diabetic macular edema as an indication for the use of aflibercept, we relied on the experience of foreign colleagues and the eye without hemorrhage was treated with five monthly loading injections of intreavitreal aflibercept 0.05 ml, and, after the first year, treatment was continued according to a “treat and extend” strategy. The case reported demonstrated that intravitreal aflibercept in combination with panretinal laser photocoagulation is effective for regression of neovascularization and prevention of recurrent vitreous hemorrhage.
Keywords: proliferative diabetic retinopathy; neovascularization; intravitreal injection; ant-VEGF agents